Original paperUsefulness of ultrasonography in differential diagnosis of gonitis - Żuber, Zbigniew; Rutkowska-Sak, Lidia; Słowińska, Iwona; Lisowska, Barbara; Ćwiek, Renata (Reumatologia/Rheumatology, 2007)
To evaluate ultrasonography (US) in assessing joint inflammation of knee. US scans obtained in 54 children with JRA, reactive arthritis and post trauma changes of the knee. Ultrasonography has been shown to be capable of substantially changing the traditional approach to most clinical problems in paediatric rheumatological practice because of its ability to allow quick, safe and inexpensive access to otherwise undetectable anatomical information on the early targets of most rheumatic diseases. Sonographic examination of the knee joint can supply important information on many pathological alterations of the periarticular soft tissues and was more sensitive than radiological examination for evaluation of treatment efficacy.